O melhoramento do cavalo lusitano : que caminhos a percorrer? - Almeida, J.P.F. (2012)
Submitted by Maria Eduarda Pereira Rodrigues (erodrigues@ipcb.pt) on 2012-07-06T16:13:56Z No. of bitstreams: 1 EQUITACAO_JPFRAGOSO.pdf: 2886808 bytes, checksum: c4e025e3892ddf290cb60e4aed6068c5 (MD5)